Characterization of modified Al, Ti–pillared clays and their adsorption potential of organic contaminants. - Đức, Trương Đình; Hương, Nguyễn Thị Thu; Bằng, Nguyễn Văn; Thu, Hoa Hữu (Vietnam Journal of Chemistry, 2012)
Natural clay minerals are well known and familiar to mankind from earliest day of civilization. Because of their low cost, abundance in most continents of the world, high adsorption properties and potential for ion-exchange, clay minerals are strong candidates as adsorption materials. In the present study, bentonite from Di Linh was used in pillared clay synthesis by use of single oxide pillars of aluminium and titannium and then modified with cetyl trimethyl ammonium bromide (CTAB). The obtained materials were characterised by XRD, TG-DTA, FT-IR, SEM and BET methods. The basal spacing of montmorillonite and the specific surface area values were increased by pillaring. Nitrogen adsorption-desorption studies and scanning electron microscopy (SEM) images confirmed that the micropore and mesopore size distributions were not affected by synthesis conditions. Their adsorption capacity was investigated with orange b-naphthol from aqueous solution controlled at room temperature.